Visiting Holocaust: Related Sites in Germany with Medical Students as an Aid to Teaching Medical Ethics and Human Rights - González-López, Esteban; Ríos-Cortés, Rosa (Conatus - Journal of Philosophy, 2019)
Some doctors and nurses played a key role in Nazism. They were responsible for the sterilization and murder of people with disabilities. Nazi doctors used concentration camp inmates as guinea pigs in medical experiments that had military or racial objectives. What we have learnt about the behaviour of doctors and nurses during the Nazi period enables us to reflect on several issues in present-day medicine (research limitations, decision making at the beginning and the end of a life and the relationship between physicians and the State). In some authors' opinions, the teaching of the medical aspects of the Holocaust could be a new model for education relating to professionalism, Human Rights, Bioethics and the respect of diversity. Teaching Medicine and the Holocaust could be a way of informing doctors and nurses of violations of Ethics in the past. Moreover, a Study Trip to Holocaust and Medicine related sites has a strong pedagogical value. Visiting Holocaust related sites, T4 centres and the places where medical experiments were carried out, has a special meaning for medical students. Additionally, tolerance, anti-discrimination, and the value of human life can be both taught and learned through this curriculum. The following article recounts our experiences of organizing and supervising a study trip with a group of medical students to some Holocaust and medicine-related sites in Berlin and Hadamar (Germany). The study tour included lectures at universities in Düsseldorf and Berlin.